2022
DOI: 10.3390/ijerph20010463
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Influencing Factors of Low-Carbon Coal Power Transition under China’s Carbon Trading Scheme: An Evolutionary Game Analysis

Abstract: To avoid the energy supply risk caused by the large-scale integration of renewable power with the grid, coal power plants with carbon capture utilization and storage (CCUS) have the potential to play an important role in the transition to a low-carbon electricity system. Based on evolutionary game theory, this study analyzed the equilibrium states, evolutionary trajectory and the corresponding critical conditions between the government and the coal power enterprises in this process. Subsequently, a numerical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…It was found that strengthening environmental supervision by local governments was an inevitable choice to promote the transformation and upgrading of the coal and power industries. Liu et al (2022) [34] analyzed the equilibrium state, evolution trajectory, and corresponding critical conditions of the government and coal power firms based on the EGT. It was found that the carbon trading scheme could directly promote the upgrading of coal and electricity, and it could be improved by establishing the electricity market trading mechanism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that strengthening environmental supervision by local governments was an inevitable choice to promote the transformation and upgrading of the coal and power industries. Liu et al (2022) [34] analyzed the equilibrium state, evolution trajectory, and corresponding critical conditions of the government and coal power firms based on the EGT. It was found that the carbon trading scheme could directly promote the upgrading of coal and electricity, and it could be improved by establishing the electricity market trading mechanism.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their research introduced a dual-market bidding model and a two-stage composite difference evolutionary game algorithm to address complex multi-party game scenarios [19]. Liu et al (2023) studied the equilibrium states, evolutionary trajectories, and critical conditions of government and coal-fired power generation companies adopting carbon capture, utilization, and storage (CCUS) technology, employing evolutionary game theory and numerical analysis [20].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The evolution of multiagent low-carbon transition has received significant attention, and scholars have conducted extensive discussions and analyses, resulting in many valuable research findings. Among them, most studies adopt the evolutionary game theory approach by constructing evolutionary game models to study the evolutionary paths and patterns of decision-making by the agents [15][16][17][18][19][20]. Evolutionary game theory, as a dynamic theory of the evolution of collective characteristics based on individual learning and selection in the interaction process, has become an essential tool for studying the agents' decision-making evolution mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous growth economists represented by Romer have revealed the critical role of technological innovation in industrial development and upgrading [31]; the experience of developed countries also proves that accelerating technological innovation is of great significance for improving the production efficiency of the fossil energy industry, reducing energy waste, and controlling environmental pollution [32]. In recent years, the Chinese government has accelerated the establishment of a technological development path for the natural gas industry, hoping that it will play a crucial role as a transitional bridge in the energy transition based on the improvement of natural gas energy development and utilization levels [33].…”
Section: Introductionmentioning
confidence: 99%